Optical properties of the Ti surface structured by femtosecond laser beam - Dolgov, L.; Kravchuk, R.; Rybak, A.; Kiisk, V.; Sildos, I.; Blonskyi, I. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2011)
Wavelength-scaled periodic ripples formed on the Ti surface under the action
of femtosecond laser irradiation have been investigated. The ripples were oriented in
parallel to the incident light polarization. After initial formation of ripples, the following
laser induced chemical transformation of metallic Ti into dielectric compound was
established using the Raman scattering data. Weak Wood’s anomaly in the spectra on
light diffracted by the structured Ti surface testifies the minor plasmonic activity.